Stakeholder Influence Strategies: An Empirical Exploration - Hendry, Jamie R. (Journal of business ethics, 2005)
In the present study, I sought to more fully understand stakeholder organizations’ strategies for influencing business firms. I conducted interviews with 28 representatives of four environmental non-governmental organizations (ENGOs): Natural Resources Defense Council (NRDC), Greenpeace, Environmental Defense (ED), and Union of Concerned Scientists (UCS). Qualitative methods were used to analyze this data, and additional data in the form of reviews of websites and other documents was conducted when provided by interviewees or needed to more fully comprehend interviewee’s comments. Six propositions derived from Frooman (1999) formed the basis for the initial data analysis; all six propositions were supported to some extent. Perhaps more interestingly, the data revealed that Frooman’s model is too parsimonious to adequately describe stakeholder influence strategies and related alliances, necessitating the development of an alternative theoretical model grounded in the data collected.